Survivability prediction based on the serum molecular fingerprint in critically ill patients - Correia, Inês (2024)
It is relevant to discover biomarkers enabling to predict critically ill patients’ survival. This study focused on 45 patients, from which 22 deceased and 23 were discharged from an Intensive Care Unit (ICU). It was considered the serum molecular fingerprint, as acquired by Fourier Transform Infra-Red (FTIR) spectroscopy, obtained 3 days before the patients discharged or death at the ICU. It was possible to obtain ratios of bands of the sera spectra, statistically different between the two groups of patients. Furthermore, good Naïve Bayes models were developed based on the second derivative spectra enabling an Area Under the Receiver Operating Characteristic Curve (AUC-ROC) of 0.77. These promising outputs suggest further investigation with a larger cohort.